2008
DOI: 10.1007/s00726-007-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Codon evolution is governed by linear formulas

Abstract: When nucleotide (G, C, T and A) contents were plotted against each nucleotide, their relationships were clearly expressed by a linear formula, y = alphax + beta in the coding and non-coding regions. This linear relationship was obtained from the complete single-stranded DNA. Similarly, nucleotide contents at all three codon positions were expressed by linear regression lines based on the content of each nucleotide. In addition, 64 codon usages were also expressed by linear formulas against nucleotide content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 36 publications
1
49
0
1
Order By: Relevance
“…5a-c). The consistent results were obtained from nucleotide alternations in various organisms (Sorimachi and Okayasu 2008a). Thus, biological evolution can be said to progress differently among different kingdoms.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…5a-c). The consistent results were obtained from nucleotide alternations in various organisms (Sorimachi and Okayasu 2008a). Thus, biological evolution can be said to progress differently among different kingdoms.…”
Section: Discussionsupporting
confidence: 71%
“…2), biological evolution progresses under this form of control in all organisms. Correlations between the contents of each nucleotide in a genome can be expressed by linear formulas (Sorimachi and Okayasu 2008a). Eukaryotes, archaea and bacteria behaved differently from each other in respect of correlations of certain amino acid concentrations with nucleotide contents (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that alternations in nucleotide content were controlled by internal biases that, in the cluster analyses, resulted in the formation of several clusters. Because nucleotide alternations are strictly governed by linear formulae in both the coding and non-coding regions [11], the codon usage pattern of an organism can be estimated by the insertion of its nucleotide content into a specific linear formula [9]. If the nucleotide alternations had occurred at random in the genomes of the selected organisms, such a clear separation between the terrestrial and aquatic vertebrates might not have been observed in the cluster analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in complete single-stranded DNA genomes, the nucleotide content alternations were strictly controlled, and were expressed by linear regression lines of nucleotide content relationships in both coding and non-coding regions [9]. In addition, Chargaff's second parity rule [10] was confirmed for a large number of complete double-stranded DNA genomes, and the nucleotide content relationships were expressed by linear formulas [11].…”
Section: Introductionmentioning
confidence: 96%